Indicadores Bacteriológicos de Poluição e sua Relação com Parâmetros Físico-Químicos em Água de Abastecimento Humano, Antes e Após o Tratamento, em Goiânia - SANTOS, Patrícia Pimentel (2010)
The city of Goiânia is supplied by Meia Ponte River and it´s tributary, the João Leite Stream, which receive significant amount of pollutant along it course, arising from population growth, farming and industrial activities. This study aimed to investigate the bacteriological and physicochemical quality of superficial waters from the river, stream and of drinking water from two water treatment plants (WTP) in Goiânia-GO. Twenty-four samples of superficial waters and 24 samples of drinking water were collected and analyzed during july 2007 and june 2008. The microbiology analysis followed the protocols established by the American Public Health Association (APHA) proceeding the determination of the Most Probably Number (MPN/100mL) of total coliform bacteria, thermotolerant coliforms, Escherichia coli, the counting of heterotrophic bacteria and the detection of Salmonella spp.. The physichochemical analysis also followed APHA´s protocols for the determination of dissolved oxygen, Biochemical Oxygen Demand, temperature, pH, chlorine residual and turbidity. Salmonella isolates were submitted to antimicrobial susceptibility tests in semiautomatic systems and serotypes were confirmed by the reference laboratory for Enterobacteriaceae of Fundação Oswaldo Cruz/RJ. Twenty-four (50.0%) samples of superficial water were above national microbiological standards and 5/24 (21.0%) were in disagreement on one or more physicochemical parameters and microbiological for class 2 freshwater. All drinking waters samples were in accordance with microbiological standards established by national legislation while 25.0% of drinking water of João Leite Stream were in disagreement to physicochemical patterns. The presence of Salmonella spp. had been detected in 3/24 (12.5%) of superficial waters samples from João Leite Stream being identified the following serotypes: Salmonella Hadar, S. Akuafo and S. Mbandaka. The strains presented intermediate susceptibility to moxifloxacin and susceptibility to ampicillin/sulbactam, ampicillin, aztreonam, cefepime, cefotaxime, ceftazidime, ceftriaxone, ciprofloxacin, imipenem, levofloxacin, meropenem, piperacillin/tazobactam, piperacillin, ticarcillin/ac. clavulanic, trimethoprim/ sulfamethoxazole. Although the half (50.0%) of untreated waters did not attend the limits established by the national legislation, after treatment, the quality of water pointed to an efficient treatment at WTP.